Access 2016 intermediate - McCrae, Ed; Safari eBooks ([Place of publication not identified] : [CompuWorks], 2016)
"This course is designed to teach students intermediate level skills in Microsoft Access 2016. In this course, students will learn to design tables for improved accuracy in data entry, review the various options to share data with other applications, learn about action queries, and review various advanced query techniques. Students will also learn how to automate processes with Macros, advanced form techniques, and advanced report techniques. This course prepares students for the Access 2016 Advanced course. "--Resource description page.
Presenter, Ed McCrae.
Title from title screen (viewed September 27, 2016).
Imprint from resource description page.
Keywords: Microsoft Access; Database management; Electronic books